2005
DOI: 10.1159/000086787
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 Protein in Esophageal Squamous Cell Carcinoma: Relation to Hypoxia-Inducible Factor-1α, Angiogenesis and Apoptosis

Abstract: Objectives: Hypoxia-inducible factor (HIF)-1 is important in the control of transcription of several genes related to angiogenesis. We have previously reported that expression of HIF-1α correlates with venous invasion and clinical outcome in esophageal squamous cell carcinoma. p53 has been reported to interact with HIF-1α and induce ubiquitin-mediated proteosomal degradation of HIF-1α. The purpose of this study was to clarify whether the expression of p53 is associated with that of HIF-1α. Methods: Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…In this regard, the combination of HIF-1a and p53 overexpression has been shown to indicate dismal prognosis in ovarian and urothelial bladder carcinomas [11,24], suggesting that HIF-1a could display a pro-apoptotic function, which would get lost in tumors with non-functional p53. Similar studies in esophageal and colorectal carcinomas, however, have not showed any association between HIF-1a and p53 and patient survival [38][39][40]. In agreement with these studies, we show here that upregulation of HIF-1a in combination with overexpression of p53 is not a factor for reduced survival in supraglottic laryngeal SCC.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, the combination of HIF-1a and p53 overexpression has been shown to indicate dismal prognosis in ovarian and urothelial bladder carcinomas [11,24], suggesting that HIF-1a could display a pro-apoptotic function, which would get lost in tumors with non-functional p53. Similar studies in esophageal and colorectal carcinomas, however, have not showed any association between HIF-1a and p53 and patient survival [38][39][40]. In agreement with these studies, we show here that upregulation of HIF-1a in combination with overexpression of p53 is not a factor for reduced survival in supraglottic laryngeal SCC.…”
Section: Discussionsupporting
confidence: 91%
“…( 11,12 ) In addition, both hypoxia and the hypoxia mimetic desferrioxamine (DFO) enhance β‐catenin transcriptional activity in osteoblasts and C3H10T1/2 cells by suppressing sclerostin and enhanced phosphorylation of GSK‐3β, respectively. ( 13,14 ) However, in the colon adenocarcinoma cell line SW480, neither β‐catenin nor TCF‐4 levels were changed in response to hypoxia and immunocytochemistry revealed no obvious changes in their subcellular localization. ( 15 ) In contrast, downregulation of β‐catenin under hypoxic conditions was observed in the human colorectal cancer cell line RKO, which may have resulted from hypoxia‐induced endoplasmic reticulum stress.…”
mentioning
confidence: 99%
“…Akt1, EGFR, and TP53 regulate proliferation, colony formation, migration, epithelial-to-mesenchymal transition, invasion, tumor microenvironment, anchorage-independent growth, and metastasis in EC cells and tumors, and they are markers for the survival rate and time. [41][42][43][44][45][46][47][48][49][50][51] GAPDH is upregulated in EC cells and tumors and promotes proliferation, invasion, migration, and chemoresistance. 52 Targeting the cytokine IL6 can repress chemoradiotherapy resistance, stemness, EMT, angiogenesis, migration, invasion, metastasis, colony formation, inflammation, and growth in EC cells and tumors.…”
Section: Discussionmentioning
confidence: 99%